Two new species and records of the genus Questa (Annelida: Orbiniidae) from Azores and Canary Islands, Central Atlantic Ocean - Núñez, Jorge; Martínez, Alejandro (Zootaxa, 2023)
We here report two new species of meiofaunal orbiniids belonging to the genus Questa Hartman, 1966, which have been discovered during benthic surveys conducted around the Azores and the Canary Islands. The new species, Q. manuelgerardi n. sp. and Questa ericnunezi n. sp., are described, figured and discussed in detail. Questa manuelgerardi n. sp., endemic from the Azores, is characterized by the lack of furcate chaetae and branchiae, and by the presence of two pairs of anal cirri. Questa ericnunezi endemic from the Canary Island, is defined by the presence of furcate chaetae, 12–18 pairs of branchiae, and two pairs of anal cirri. In addition, new records of the species Q. caudicirra Hartman, 1966 are provided. An identification key to the 12 known species of Questa is also included.